Analysis of maintenance outsourcing from the perspective of costs and economic impacts: bibliographic review - Mamede, Ana Luíza Ferreira; Resende, André Alves de (Brazilian Journal of Production Engineering, 2021)
The concept of process outsourcing brings with it, automatically, the idea of economic gain for the contracting company. However, outsourcing involves several important aspects, such as legality, quality, security, availability, among others. In this way, it becomes necessary to evaluate in detail the advantages and disadvantages that will be obtained with the outsourcing process, according to the sector and the activity that will be outsourced, so as to understand how it will impact the company economically. Maintenance activity is usually a middle activity, so it is very common for it to be outsourced. Faced with this, the present work consists of a literature review based on bibliographic research in order to analyze the outsourcing of maintenance with a focus on costs and economic impacts. The results found proved that the outsourcing process will not always be economically advantageous for organizations.
Keywords: Outsourcing; maintenance; costs